Coastal Tourism Enhancement and Waste Management Initiative in Negeri Ureng, Central Maluku - Fransina S. Latumahina; Surya Bagaskara Bagus Dermawan Putra; Zalfa Zakiyah Buamona; Sri Rizky Serwan Mualo (Universitas Muhammadiyah Sidoarjo, 2023)
This study assesses the implementation of a community-led tourism exploration and beach cleaning initiative in Negeri Ureng, Central Maluku, particularly in Island 3 Nusa Ela. Our goal was twofold: firstly, to explore and identify new tourism sites and, secondly, to foster a greater understanding and action towards coastal waste management. The adopted method incorporated community engagement, direct observation, and active participation in waste cleanup activities. Findings highlighted picturesque sites around Island 3 Nusa Ela, such as the vicinity near the villa at the island's end, and a unique fresh water source in a large cave. However, the cleanup activities revealed a significant amount of poorly managed waste, predominantly plastic, along the coastline, thus necessitating immediate waste management strategies. As a result, signage was installed to educate both locals and visitors about the adverse impacts of improper waste disposal on the ecosystem and coastal aesthetics. The study underscores the vital role of community involvement in preserving and enhancing coastal areas while showcasing its potential for sustainable tourism. This initiative bears significant implications for other coastal communities worldwide striving to strike a balance between tourism development and environmental conservation.Highlights: Tourism Locations: The study identified scenic tourism sites in Island 3 Nusa Ela. Waste Management: The cleanup revealed significant plastic waste along the coastline, necessitating immediate intervention. Environmental Education: Signage was used to educate locals and visitors on the importance of proper waste disposal. Keywords: Coastal Tourism, Waste Management, Negeri Ureng, Community Initiative, Environmental Preservation.